THE EFFECT OF FOOT STRENGTH AND SPEED TRAINING ON THE RESULTS OF THE EXTRACURICULAR ATHLETICATHLETIC LEVEL OF MTs. HIDAYATUL MUBTADI`IN BANYUWANGI DISTRICT - Ach. Zayul Mustain (MAN Insan Cendekia Jambi, 2021)
Athletics is the oldest sport owned by humans, because its basic movements have been reflected in human life for a long time, namely walking, running, jumping and throwing. Athletics is a sport that underlies another sport of Florence in Maulana (2016). Furthermore, according to Bakar (2019) athletics is an effective physical activity to optimize children's growth and development. One of the categories of athletics, especially in jump numbers, is multi-jump. The type of research used in this study is a quasi experiment. According to Suharsimi Arikunto (2010), states that experimental research is research that is intended to determine whether or not there is a consequence of